Dietary Variability During Bronze Age in Central Italy: First Results. (4th March 2015) - Varalli, A.; Moggi‐Cecchi, J.; Moroni, A.; Goude, G.
Abstract: This research aims at delineating the dietary practices in Central Italy during the Bronze Age. The study of food choices is a mean for investigating palaeoenvironmental agricultural and economic activities and social relationships, which have been little explored until now in Italy from this specific perspective. Recent researches have showed that the Middle Bronze Age is a crucial period of dietary changes in Italy. Following these first observations, we studied three Bronze Age sites in Tuscany and Latium: Grotta dello Scoglietto, Grotta Misa and Felcetone. Analyses of stable carbon, nitrogen and sulphur isotopes on 38 human and 22 animal collagen samples were performed. The results show three different dietary patterns. Data from Grotta dello Scoglietto (Early Bronze Age) indicate a high‐protein intake, with a probable consumption of fish. Additionally, sulphur results let us infer the presence of some non‐local people. Individuals from Felcetone (Initial phase of the Middle Bronze Age) show a terrestrial diet dominated by plant proteins, which suggests a low δ 15 N food intake, namely legumes, as well as C4 plant, such as millet. Finally, values from Grotta Misa (Middle Bronze Age) highlight a mixed terrestrial diet and the consumption of millet. Given the variety of the obtained results, we are able to conclude that the transition from the Early to the Middle Bronze Age represents a moment of change, which is reflected by the presence of different dietary patterns. Copyright © 2015 John Wiley & Sons, Ltd.